2017
DOI: 10.1016/j.cgh.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Diets of Patients With Nonceliac Gluten Sensitivity Compared With Healthy Individuals

Abstract: In an observational study, we found that patients with NCGS eat different foods than healthy individuals; patients consume lower levels of proteins, carbohydrates, fiber, and polyunsaturated fatty acids. Their diets should be routinely analyzed and possibly corrected to avoid nutritional deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…However, in regards to gender, thyroid disease, IBS, and celiac disease in close family, our sample was very much alike the samples described in other challenge and cross-sectional studies. 12,13,15,[40][41][42] Further, we did not find any effect of any of these factors on the challenge outcome. Regarding adequate exclusion of celiac disease and celiac disease serology, our sample was more homogenous than in previous challenge studies.…”
Section: Discussioncontrasting
confidence: 55%
“…However, in regards to gender, thyroid disease, IBS, and celiac disease in close family, our sample was very much alike the samples described in other challenge and cross-sectional studies. 12,13,15,[40][41][42] Further, we did not find any effect of any of these factors on the challenge outcome. Regarding adequate exclusion of celiac disease and celiac disease serology, our sample was more homogenous than in previous challenge studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, further investigation of whether this strict adherence is necessary in this patient group is of great importance due to the knowledge of the GFD potentially not being nutritionally adequate. A recent study investigated the diet and nutritional characteristics of patients with NCGS and found that these patients eat different foods than healthy individuals, and consumed lower levels of protein, carbohydrates, fiber, and polyunsaturated fatty acids, thus the diet of this patient group should be routinely analysed to avoid nutritional deficiencies …”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated the diet and nutritional characteristics of patients with NCGS and found that these patients eat different foods than healthy individuals, and consumed lower levels of protein, carbohydrates, fiber, and polyunsaturated fatty acids, thus the diet of this patient group should be routinely analysed to avoid nutritional deficiencies. 26 It has been frequently hypothesized that NCGS cannot be separated from IBS as a unique diagnosis, but is rather presented as a sub-group of IBS. The amount of FODMAPs in the diet is most likely a contributor to symptoms in patients believing to have NCGS, and the relationship between NCGS and IBS needs to be investigated in further studies.…”
Section: Ncgsmentioning
confidence: 99%
“…The NHANES participants on a gluten-free diet had higher urinary arsenic and serum mercury concentrations compared to individuals on regular gluten-containing diet (18). Another nutritional study of gluten-free diet found that individuals with NCGS eat fewer carbohydrates but also decrease intake of fiber, polyunsaturated fatty acids, folic acid, vitamin B6, zinc, and magnesium compared to individuals on a regular diet (19,20). Thus, if a gluten-free diet is trialed, nutritional counseling will be needed to help women maintain a balanced gluten-free diet.…”
Section: Discussionmentioning
confidence: 99%
“…While a gluten-free diet is the definitive treatment for celiac disease, the duration of adherence to a gluten-free diet is also unclear for individuals with NCGS. Currently, there is no evidence of a gluten-free diet being healthier than a gluten-containing diet (17)(18)(19)(20). Inadequate intake of fiber, B vitamins, magnesium, calcium, and zinc has been reported with a gluten-free diet (17).…”
Section: Discussionmentioning
confidence: 99%